High-throughput modelling and structural investigation of cysteine protease complexes with protein inhibitors - Kroon, Matthys Christoffel (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
The papain-like cysteine protease family (C1 proteases) is highly important because of its involvement in research and industrial applications and its role in various human diseases. Protein inhibitors are an important aspect of C1 protease biology and are relevant to its clinical, industrial and research importance. To study the interaction between the proteases and the inhibitors it is very useful to have accurate structural models of the protease-inhibitor complexes. To this end, a high-throughput pipeline for modelling complexes of papain-like cysteine proteases and protein inhibitors was implemented and tested (Tastan Bishop & Kroon, 2011). The pipeline utilizes a novel technique for obtaining modelling templates by using superpositioning to combine coordinates from separate experimental structures. To test the pipeline, models of complexes with known structures (test set) were modelled using many different templates and the resultant models evaluated to compare the quality of the different templates. It was found that use of the new technique to obtain templates did not introduce significant errors, while allowing closer homologs to be used for modelling - leading to more accurate models. The test set models were also used to evaluate certain steps of the modelling protocol. The effect of Rosetta energy minimization on model accuracy and the use of Rosetta energy and DOPE Z-score values to identify accurate models were investigated. Several complexes were then modelled using the best available templates according to criteria informed by the previous results. A website was built that allows a user to download any of the metrics or models produced in the study. This website is accessible at http://rubi.ru.ac.za/cpmdb
Keywords: Cysteine proteinases; Cysteine proteinases -- Inhibitors; Papain; Cystatins; Malaria -- Chemotherapy; Homology (Biology); Protein-protein interactions